2021
DOI: 10.1140/epjp/s13360-021-01411-1
|View full text |Cite
|
Sign up to set email alerts
|

LABEC, the INFN ion beam laboratory of nuclear techniques for environment and cultural heritage

Abstract: The LABEC laboratory, the INFN ion beam laboratory of nuclear techniques for environment and cultural heritage, located in the Scientific and Technological Campus of the University of Florence in Sesto Fiorentino, started its operational activities in 2004, after INFN decided in 2001 to provide our applied nuclear physics group with a large laboratory dedicated to applications of accelerator-related analytical techniques, based on a new 3 MV Tandetron accelerator. The new accelerator greatly improved the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Radiocarbon dating was performed by Accelerator Mass Spectrometry using the dedicated beam line of the HVEE 3 MV Tandem accelerator installed at the INFN-LABEC laboratory in Florence [26,27]. Before the measurements, the sample was prepared using the Acid-Base-Acid procedure [28] to remove the possible natural contaminations from exogenous carbon.…”
Section: Radiocarbon Dating By Accelerator Mass Spectrometry (Ams)mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiocarbon dating was performed by Accelerator Mass Spectrometry using the dedicated beam line of the HVEE 3 MV Tandem accelerator installed at the INFN-LABEC laboratory in Florence [26,27]. Before the measurements, the sample was prepared using the Acid-Base-Acid procedure [28] to remove the possible natural contaminations from exogenous carbon.…”
Section: Radiocarbon Dating By Accelerator Mass Spectrometry (Ams)mentioning
confidence: 99%
“…Molecules 2021,26, 5268 12 of 15 calibration curve (conventional radiocarbon age vs. calendar age) with its uncertainty is shown in blue; the measured radiocarbon age, treated as a normally distributed random variable, is displayed in red on the y axis. The calibration result is reported in grey on the x axis as posterior probability distribution.…”
mentioning
confidence: 99%
“…The second part of the filter was analyzed by PIXE which allowed the measurement of the concentrations of all the elements with atomic number Z > 16. The analyses were carried out with the 3 MV Tandetron accelerator of the LABEC laboratory in Florence with the external set-up described in Lucarelli et al (2018Lucarelli et al ( , 2014, Chiari et al (2021), Calzolai et al (2006). Using uncertainties on elemental concentrations were determined by the sum of independent uncertainties on certified thicknesses of the standards (5%), deposition area (2%), air flow (2%), and X-ray counting statistics (2%-20%).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Tests of detectors for nuclear and particle physics [1][2][3], studies of ion-matter interaction for solid state physics [4] and compositional measurements for heritage science (HS) [5], and environmental aerosol science [6] are just some examples of the diverse applications. Those activities have been conducted thanks to the six beamlines of the TANDETRON accelerator: the external beamline for aerosol measurements [7]; the external microbeam line [8]; the pulsed beamline [9,10]; the ion beam analysis beamline in vacuum [11]; the external beamline for cultural heritage measurements; and the atomic mass spectrometry beamline for 14 C dating [12]. Reviews on past and current activities at the INFN-LABEC are found in [13,14].…”
Section: Introductionmentioning
confidence: 99%